2024
DOI: 10.1186/s12941-024-00675-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of multidrug-resistant bacterial infection in non-cystic fibrosis bronchiectasis

Chih-Hao Chang,
Chiung-Hsin Chang,
Shih-Hao Huang
et al.

Abstract: Purpose Multidrug-resistant (MDR) bacteria impose a considerable health-care burden and are associated with bronchiectasis exacerbation. This study investigated the clinical outcomes of adult patients with bronchiectasis following MDR bacterial infection. Methods From the Chang Gung Research Database, we identified patients with bronchiectasis and MDR bacterial infection from 2008 to 2017. The control group comprised patients with bronchiectasis wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Post hoc analysis of the BLESS randomised controlled trial (RCT) showed that erythromycin treatment altered the microbiome with displacement of H. influenzae by macrolide-tolerant pathogens such as P. aeruginosa [ 50 ], which is one of many bacteria capable of virulence adaptations conferring resistance to antibiotic treatment [ 51 ]. Multidrug-resistant organisms are common in bronchiectasis and are associated with more severe exacerbations and higher mortality, both in prospective and retrospective analyses [ 52 , 53 ].…”
Section: The Pathophysiology Of Bronchiectasis Exacerbationsmentioning
confidence: 99%
“…Post hoc analysis of the BLESS randomised controlled trial (RCT) showed that erythromycin treatment altered the microbiome with displacement of H. influenzae by macrolide-tolerant pathogens such as P. aeruginosa [ 50 ], which is one of many bacteria capable of virulence adaptations conferring resistance to antibiotic treatment [ 51 ]. Multidrug-resistant organisms are common in bronchiectasis and are associated with more severe exacerbations and higher mortality, both in prospective and retrospective analyses [ 52 , 53 ].…”
Section: The Pathophysiology Of Bronchiectasis Exacerbationsmentioning
confidence: 99%
“…In addition to these challenges, the efficiency of antibiotic treatments may be impaired due to the emergence of antibiotic resistance and delayed drug response. For instance, methicillin-resistant Staphylococcus aureus (MRSA) and carbapenem-resistant Enterobacteriaceae (CRE) are examples of antibiotic-resistant bacteria that complicate sepsis treatment, leading to higher mortality rates ( 8 , 21 ). These resistant strains are not effectively killed by standard antibiotics, necessitating the use of alternative or combination therapies, which may not always be readily available or as effective.…”
Section: Introductionmentioning
confidence: 99%